Enhancing fetal outcomes in GCK-MODY pregnancies: a precision medicine approach via non-invasive prenatal GCK mutation detection - Schwitzgebel, Valérie M.; Blouin, Jean-Louis; Dehos, Barbara; Köhler-Ballan, Bettina; Puder, Jardena J.; Rieubland, Claudine; Triantafyllidou, Maria; Zanchi, Anne; Abramowicz, Marc; Nouspikel, Thierry (Frontiers in Medicine, 2024)
Background Mutations in the GCK gene cause Maturity Onset Diabetes of the Young (GCK-MODY) by impairing glucose-sensing in pancreatic beta cells. During pregnancy, managing this type of diabetes varies based on fetal genotype. Fetuses carrying a GCK mutation can derive benefit from moderate maternal hyperglycemia, stimulating insulin secretion in fetal islets, whereas this may cause macrosomia in wild-type fetuses. Modulating maternal glycemia can thus be viewed as a form of personalized prenatal therapy, highly beneficial but not justifying the risk of invasive testing. We therefore developed a monogenic non-invasive prenatal diagnostic (NIPD-M) test to reliably detect the transmission of a known maternal GCK mutation to the fetus. Methods A small amount of fetal circulating cell-free DNA is present in maternal plasma but cannot be distinguished from maternal cell-free DNA. Determining transmission of a maternal mutation to the fetus thus implies sequencing adjacent polymorphisms to determine the balance of maternal haplotypes, the transmitted haplotype being over-represented in maternal plasma. Results Here we present a series of such tests in which fetal genotype was successfully determined and show that it can be used to guide therapeutic decisions during pregnancy and improve the outcome for the offspring. We discuss several potential hurdles inherent to the technique, and strategies to overcome these. Conclusion Our NIPD-M test allows reliable determination of the presence of a maternal GCK mutation in the fetus, thereby allowing personalized in utero therapy by modulating maternal glycemia, without incurring the risk of miscarriage inherent to invasive testing.